2014
DOI: 10.2147/nrr.s44751
|View full text |Cite
|
Sign up to set email alerts
|

Pleural mesothelioma: management updates and nursing initiatives to improve patient care

Abstract: Malignant pleural mesothelioma is a relatively rare but aggressive malignancy that is primarily associated with occupational asbestos exposure. While treatment options for mesothelioma have expanded, the disease carries a poor prognosis, with a median of 8 months to 1 year of survival postdiagnosis. This article synthesizes current disease-management practices, including the diagnostic workup, treatment modalities, emerging therapies, and symptom management, and identifies comprehensive nursing strategies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 81 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…24 48 Four reviews took other approaches: meta-ethnographic, 6 selective, 57 scoping 27 and unidentified. 58 Overall, the review studies had clearly stated questions, with appropriate inclusion criteria, search strategies and synthesis methods. They all used the reported data to make recommendations for policy and/or practice and to specify directives for new research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 48 Four reviews took other approaches: meta-ethnographic, 6 selective, 57 scoping 27 and unidentified. 58 Overall, the review studies had clearly stated questions, with appropriate inclusion criteria, search strategies and synthesis methods. They all used the reported data to make recommendations for policy and/or practice and to specify directives for new research.…”
Section: Resultsmentioning
confidence: 99%
“… 33 37 38 54 63 64 Patients and carers often mourned their previous life 63 and experienced anticipatory grief. 58 …”
Section: Resultsmentioning
confidence: 99%
“…Mitsuhashi and Toda (2011) reported that quiet terminally ill patients were often in extreme spiritual pain; MPM patients with such pain kept away from health care staff and family members . The care of patients with spiritual pain is difficult and causes suffering among nurses (Lehto, 2014). reported that nurses experienced strong distress when attempting to communicate with patients with MPM who could not accept their disease and prognosis.…”
Section: Communication Skill Needsmentioning
confidence: 99%
“…reported that nurses experienced strong distress when attempting to communicate with patients with MPM who could not accept their disease and prognosis. In addition, improving the relationship between patients with MPM and their family requires sensitivity in fully understanding the multiple causal factors together with the ability to empathize and use appropriate communication skills to facilitate reconciliation (Lehto, 2014). In conducting programs in the future, an additional module on communicating with patients in spiritual suffering and managing nurses' compassion fatigue (Lombardo and Eyre, 2011) should be considered.…”
Section: Communication Skill Needsmentioning
confidence: 99%
See 1 more Smart Citation